TECHNOLOGICAL PEDAGOGICAL AND CONTENT KNOWLEDGE (TPACK) PERCEPTION OF ENGLISH EDUCATION STUDENTS - Mitha Septiyanti; Rita Inderawati; Machdalena Vianty (University of Kuningan, 2020)
Abstract: Technological Pedagogical and Content Knowledge, abbreviated as TPCK or TPACK, is the interdependent, situated knowledge needed to integrate the use of digital tools and resources effectively in curriculum-based teaching. This study aims to find out the TPACK perception of English Education students at Lampung University, the way the students obtain TPACK in learning, and the role of lecturers in assisting the students to obtain TPACK in learning. By applying a mixed method, questionnaire and interview were used to gather the data. 225 English Education undergraduate students in academic year 2018/2019 and 3 lecturers participated in this study. As result, the TPACK perception of the students was generally good as the score of all domains measured (Technological Knowledge/TK, Technological Content Knowledge/TCK, Technological Pedagogical Knowledge/TPK, Technological Pedagogical Content Knowledge/TPCK, and Technology-related Learning Experiences/TLE) was 722.1. Moreover, the students obtained TPACK by observing lecturers teaching in the classroom and doing self-learning with internet as media. Further, it was found that there were five roles of the lecturers in assisting the students to obtain TPACK in learning, namely provider, model, controller, facilitator, and motivator.Keywords: TPACK; English dducation students; role of lecturers; students’ learning; ICT.